The role of multi-parametric MRI in loco-regional staging of men diagnosed with early prostate cancer. Issue 6 (November 2015) - Appayya, Mrishta Brizmohun; Johnston, Edward William; Punwani, Shonit
<x xml:space="preserve">Abstract</x> Purpose of review To review the use of multi-parametric MRI (mpMRI) in loco-regional assessment of men with early prostate cancer. Recent findings mpMRI comprises anatomic T2 and T1 sequences supplemented by functional imaging techniques such as diffusion-weighted and dynamic contrast enhanced (DCE) imaging. mpMRI is gaining increasing acceptance for prostate cancer detection and staging of early disease. It can facilitate targeted therapies, guide surgical options and enable active surveillance within suitable patients. The technique can be performed at 1.5 or 3 Tesla, but sequence optimization is critical to successful implementation of mpMRI. T2 and diffusion-weighted sequences are minimal requirements and are often complemented by DCE images. When performed at high spatial resolution, DCE facilitates detection of disease, as well as assessment of extra-capsular extension, distal urethral sphincter and seminal vesicles involvement. Pre-biopsy mpMRI is recommended for both detection and staging as it avoids biopsy artefact, and when normal, has a negative predictive value of 95% for significant cancer. Summary mpMRI reliably detects clinically significant prostate tumour and ideally should be performed prior to biopsy. It provides an accurate method for local disease staging and facilitates a growing range of treatment options for patients with early disease.